Undergraduate's motivation and issues for online shopping / Nurul Amira Md Lazan - Md Lazan, Nurul Amira (2012)
Online shopping was introduced to the market in the last decade as many individuals and organizations purchase through the Internet. Online shopping offers the Internet users a wider range of benefit that can motivate them to shop online. However, various issues can appear to affect the adoption of online shopping. This study sets out to identify the undergraduate's motivations and issues for online shopping at FSKM UiTM Shah Alam through a 5-point Likert Scale questionnaire. A sample of 140 students was selected among computer science undergraduates at FSKM UiTM Shah Alam. The data analysis is done by using SPSS software and the technique that used is descriptive statistics and mean comparisons. The results of the study found four motivational factors that are accessibility factor, reliability factor, convenience factor and distribution factor which motivate students to shop online. This study also identifies six issues that make students refuse to shop online. The issues are privacy issue, reluctance to change issue, quality issues, security issue, trust issue, and payment issue. It is concluded that online retailers should concern with all issues for online shopping in order to attract existing users of the Internet to shop online.